Survey of deployment algorithms in wireless sensor networks: coverage and connectivity issues and challenges. (2017) - Khoufi, Ines; Minet, Pascale; Laouiti, Anis; Mahfoudh, Saoucene
Wireless sensor networks (WSNs) have many fields of application, including industrial, environmental and military domains. Monitoring a given zone is one of the main goals of this technology. This consists in deploying sensor nodes in order to detect any event occurring in the zone and report it to the sink. We present a survey that focuses on coverage and connectivity issues in WSNs. We motivate our study by giving different use cases corresponding to different coverage, connectivity, latency and robustness requirements of the applications considered. We present a general and detailed analysis of deployment problems, while highlighting the impacting factors, the common assumptions and models adopted in the literature, as well as performance criteria for evaluation purposes. Different deployment algorithms for area, barrier, and points of interest are studied and classified according to their characteristics and properties. Before concluding, we look at current trends and discuss some open issues.